Novel milk ingredient blend in nursery pig diets did not improve growth performance and survival compared to control diets without or with spray-dried plasma - Shen, Yanbin; Kim, Sung Woo; Stein, Hans H.; Polo, Javier; Crenshaw, Joe (Frontiers in Animal Science, 2025)
Three experiments evaluated the effects of a novel milk ingredient blend (FXP) in phase 1 and 2 nursery pig diets on growth performance, diarrhea score, and survival. In Experiment 1, pigs were fed a 3-phase nursery regimen, with phases 1, 2, and 3 lasting 10, 11, and 6 days, respectively. Treatments included a control diet in each phase (CONTROL), 4% spray-dried plasma (SDP) in phase 1 followed by the CONTROL diet in phases 2 and 3 (SDP), and 0.5% FXP in phases 1 and 2, followed by the CONTROL diet in phase 3 (FXP). There were 8, 9, and 10 pens assigned to the CONTROL, SDP, and FXP treatments, respectively. Pigs fed SDP during phase 1 had greater (P < 0.05) average daily gain (ADG), average daily feed intake (ADFI), and average body weight (BW) on day 10 than pigs fed the CONTROL or FXP treatments, and a greater (P < 0.05) gain-to-feed ratio (G:F) than pigs fed the FXP diet. In Experiment 2, the 3-phase nursery feed regimen consisted of diets fed for 11, 10, and 21 days in phases 1 to 3, respectively, using the same treatments as in Experiment 1: CONTROL, 4% SDP in phase 1 only, and 1% FXP in phases 1 and 2. Each treatment included 12 pens. Pigs fed SDP in phase 1 had significantly greater (P < 0.05) ADG, ADFI, and BW on day 11 than those fed CONTROL or FXP diets. Cumulative mortality by day 21 was higher (P < 0.05) for pigs fed FXP compared with CONTROL and SDP, and fecal score was lower (P < 0.05) for SDP compared with CONTROL. In Experiment 3, pigs were assigned to either a CONTROL or FXP group, with 0.5% FXP included only in phases 1 and 2. Phases 1 to 3 lasted 11, 12, and 19 days, respectively. Each treatment was assigned to 64 pens of 25–26 pigs per pen. Pigs fed FXP had a higher (P < 0.05) removal rate during phase 3 than the CONTROL. Overall, there were no benefits from feeding 0.5% to 1% FXP on pig growth performance, diarrhea incidence, or survival based on the results from these experiments.